Climate change mitigation discourses in the institutional instruments that shape catchment governance in Queensland, Australia. Issue 3 (3rd July 2022) - McIlwain, Lisa; Baldwin, Claudia; Manathunga, Catherine; Baird, Julia; Pickering, Gary
ABSTRACT: Agriculture and Land Use, Land-Use Change and Forestry (LULUCF) sectors account for almost 25 per cent of global greenhouse gas emissions through livestock farming, land clearing, and land use activities such as cropping, changing grassland into settlement or deforestation. The LULUCF is a key sector for carbon sink capacity. Despite desperate need for stronger climate change mitigation efforts, there has been little attention paid to the institutional instruments that govern the mitigation potential of the agriculture and LULUCF sectors in Australia. Using Australia's Lockyer Valley catchment in Queensland as an example, this study investigates the dominant discourses about climate change that are conveyed in the institutional instruments (legislation, policies, strategies, and plans) that apply to catchment scale governance. We employ Bacchi's approach to policy analysis, to understand the dominant discourses, silences, and underlying power dynamics that shape institutional instruments in a catchment setting. The key findings reveal (1) a discourse that is alert to the impacts of climate change while largely ignoring its link to greenhouse gas emissions; (2) a pronounced silence about emissions from agriculture and LULUCF in institutional instruments; and (3) a general development paradigm that couples economic growth with carbon emissions.